Pedagogical beliefs and practices of teachers of high and low performing pupils in elementary mathematics - Hofer, George S. (2006)
This research sought to determine the difference in the beliefs and teaching practices of public school elementary mathematics teachers of high and low performing students in the Division of Cotabato City. Thirty-three Grade V mathematics teachers served as the sample of the study. 299 pupils of these teachers were randomly selected to determine who were high performing and low performing. A mathematics performance test was given to the pupils after the unit topics found in the course outline were taught. There was no significant difference found in the teaching beliefs and practices of teachers of high performing students and those of low performing students. They believe that active participation in the teaching and learning process helps students learn best about the subject matter. Beliefs about mathematics and teaching are more pronounced among teachers of low performing students while teachers of high performing students are more inconsistent in their teaching strategies.
Thesis (M.A. Mathematics Education)--University of the Philippines, Diliman.
Keywords: Mathematics -- Study and teaching (Elementary) -- Philippines -- Cotabato City (Maguindanao); Mathematics teachers -- Philippines -- Cotabato City (Maguindanao); Mathematical ability -- Testing; School children -- Philippines -- Cotabato City (Maguindanao)